The Influence of Audit Quality, Financial Condition, and Good Corporate Governance Mechanisms on Going Concern Audit Opinions with Company Size as a Moderating Variable - Neneng Widayati; Parlindungan Dongoran; Siti Hawa; Tita Safitriawati; Amanda Khoirunnisa (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2023)
This research aims to analyze the influence of audit quality, financial conditions, and good corporate governance mechanisms on going concern audit opinions with company size as a moderating variable in property & real estate subsector companies listed on the Indonesia Stock Exchange in 2017-2021. The population in this research is 80 property & real estate companies registered on the IDX in 2017-2021. The technique used was purposive sampling, the sample from this research was 18 companies. This research uses a method with a quantitative approach, namely analyzing data using logistic regression and processing it using IBM SPSS Statistics 25 software. The results obtained in this research are that audit quality has no effect on going concern audit opinion, financial conditions have a significant effect on going concern audit opinion. concern, good corporate governance mechanisms have no significant effect on going concern audit opinion, company size does not moderate the relationship between audit quality and going concern audit opinion, company size moderates the relationship between financial condition and going concern audit opinion, and company size does not moderate the relationship between mechanisms good corporate governance on going concern audit opinion.